2006
DOI: 10.1097/01.ico.0000214204.22200.7f
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Contact Lens Storage Solutions against Different Acanthamoeba Strains

Abstract: Two of the tested contact lens solutions (the ones for rigid gas permeable lenses) destroyed the cysts of all strains. One of these, containing a combination of two amoebicidal ingredients even after only one hour of exposure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…While the underlying mechanism for this risk remains unknown, none of the widely-used multipurpose solutions have been shown to be highly efficacious against Acanthamoeba; however they have generally been adequate to suppress large AK outbreaks in the past. 8,[30][31][32][33][34][35][36] This suggests the risk presented by use of Complete MoisturePlus may be a relative inability to withstand an Acanthamoeba challenge compared to that of other solutions. Results similarly demonstrate non-statistically significant patterns of risk suggesting hygiene-and potentially water-related factors such as showering with contact lenses may contribute to AK.…”
Section: -58mentioning
confidence: 99%
“…While the underlying mechanism for this risk remains unknown, none of the widely-used multipurpose solutions have been shown to be highly efficacious against Acanthamoeba; however they have generally been adequate to suppress large AK outbreaks in the past. 8,[30][31][32][33][34][35][36] This suggests the risk presented by use of Complete MoisturePlus may be a relative inability to withstand an Acanthamoeba challenge compared to that of other solutions. Results similarly demonstrate non-statistically significant patterns of risk suggesting hygiene-and potentially water-related factors such as showering with contact lenses may contribute to AK.…”
Section: -58mentioning
confidence: 99%
“…Trophozoites in exponential growth (72 to 96 h) were concentrated by centrifugation at 500×g for 10 min. The amoebas were washed twice in sterile Neff's saline solution (1.2 g NaCl, 0.4 g MgSO 4 ·H 2 O, 0.4 g CaCl 2 ·2H 2 O, 1.42 g Na 2 HPO 4 , and 1.36 g KH PO 4 in 100 ml distilled water), counted in a hemacytometer, adjusted to final concentrations in Neff's saline solution at a density of 10 4 amebae/ml (Hiti et al 2006) (95% trophozoites), and used immediately for testing.…”
Section: Parasites and Culturementioning
confidence: 99%
“…In Thailand, a study showed that about 5% of cases occur in contact lenses wearers (Preechawat et al 2007). The use of effective contact lens solutions and adequate disinfection times are a fundamental method of preventing corneal infection by Acanthamoeba (Beattie et al 2003;Hiti et al 2006;Kilvington and Anger 2001;Niszl and Markus 1998). The clinical symptoms of AK are similar to those of herpes simplex keratitis and fungal keratitis (Bacon et al 1993;Mathers et al 1996), so this condition can easily be misdiagnosed.…”
Section: Introductionmentioning
confidence: 99%